Effect of Cardiac Rehabilitation Program\'s First Phase on Anxiety in Patients with Coronary Arteries Bypass Surgery - A.A Asadi Noughabi; M Shaban; S Faghihzadeh; M Asadi (Tehran University of Medical Sciences, 2009)
Background & Aim: It is important to measure the anxiety level in patients who undergo heart surgery and find out ways to relief it. This study aimed to determine the effect of cardiac rehabilitation program's first phase on the level of anxiety among patients hospitalized for coronary arteries bypass surgery. Methods & Materials: In this randomized clinical trial, sixty patients were selected using block sampling and randomly allocated into experimental and control groups. Data were gathered using a questionnaire including the spiel burger's standardized questionnaire. The level of anxiety was measured in both groups. Then, the first phase of cardiac rehabilitation program (including physical exercise, and daily living activities) was carried out in the experimental group. Finally, patients in the experimental group discussed their experiences of surgery. Control group Patients received usual care. The level of anxiety was measured in both groups the day before surgery and at the time of discharge. Data were analyzed using t-test, chi-square, and Friedman tests in SPSS. Results: Findings showed that the level of anxiety had no significant differences between two groups at the time of admission. After implementing the rehabilitation program, the level of anxiety decreased significantly (P<0.001) in the experimental group. Significant differences were observed in the level of anxiety between two groups after intervention (P=0.015) and at the time of discharge (P=0.038). Conclusion: This procedure should be used in surgery patients